Identification and biochemical characterization of resistance against downy mildew in snapmelon - PARVINDER SINGH SEKHON; ASTHA, SITA KHANAL* (Indian Phytopathology, 2017)
Snapmelon downy mildew, an important foliar disease caused by Pseudoperonospora cubensis is an obligate parasite, which can survive and reproduce on living host tissue, causing significant yield losses. Forty six accessions of snapmelon were screened against P. cubensis in the cropping season 2015 and 2016. Plants were inoculated at optimum level of sporangial suspension (4.0 Â´ 104 sporangia per ml) to create downy mildew. Out of forty six accessions, three were resistant having incidence in the range of 20-30 per cent and rest were moderately resistant, moderately susceptible, susceptible and highly susceptible. Significant mean maximum disease severity was observed in snapmelon accession SM 2013-7 and minimum in accession MC 2013-4. For further confirmation, biochemical studies of various defense enzymes were carried out in resistant accessions and compared with susceptible. The data pertaining to the activity of peroxidase, catalase, phenylalanine ammonia lyase and total phenols revealed significant differences (p=0.05) among the different accessions of snapmelon showing different reactions against P. cubensis. Higher activity of all those antioxidant enzymes were observed in resistant, followed by moderately resistant whereas activity gradually declined among susceptible and highly susceptible accessions. Negative values of Pearsonâ€™s correlation coefficient were obtained between antioxidant enzyme activity and disease development suggesting possible involvement of these enzymes in imparting disease resistance against downy mildew in snapmelon. The narrow genetic base of modern snapmelon accessions and a few sources of resistance make downy mildew resistance an important objective in snapmelon breeding programs. Thus, improving the genetic resistance of snapmelon to downy mildew through introgressive breeding could be an effective way to control this disease.